2021
DOI: 10.2196/25513
|View full text |Cite
|
Sign up to set email alerts
|

A Multiple Health Behavior Change, Self-Monitoring Mobile App for Adolescents: Development and Usability Study of the Health4Life App

Abstract: Background The link between chronic diseases and the Big 6 lifestyle risk behaviors (ie, poor diet, physical inactivity, smoking, alcohol use, sedentary recreational screen time, and poor sleep) is well established. It is critical to target these lifestyle risk behaviors, as they often co-occur and emerge in adolescence. Smartphones have become an integral part of everyday life, and many adolescents already use mobile apps to monitor their lifestyle behaviors and improve their health. Smartphones m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 65 publications
(110 reference statements)
4
40
0
1
Order By: Relevance
“…Capabilityrelated facilitators to the uptake of online services targeting SNAP risk behaviours involved a desire to try and learn something new and that online services complemented the advice/support received from telephone services. The finding that online support services would help with learning something new is similar to prior research with adolescents [41]. The finding that online services complement advice/support from telephone services is consistent with the study by Lal et al, where participants indicated a preference for support to be offered via different modalities [42].…”
Section: Discussionsupporting
confidence: 87%
“…Capabilityrelated facilitators to the uptake of online services targeting SNAP risk behaviours involved a desire to try and learn something new and that online services complemented the advice/support received from telephone services. The finding that online support services would help with learning something new is similar to prior research with adolescents [41]. The finding that online services complement advice/support from telephone services is consistent with the study by Lal et al, where participants indicated a preference for support to be offered via different modalities [42].…”
Section: Discussionsupporting
confidence: 87%
“…Studies in which students were invited to participate by cocreating an intervention appeared to be potentially more effective [17][18][19]. Actively involving students using dialog about their perspectives on lifestyle seems to lead to more acceptable and effective interventions [20,21]. It is important to focus on what they enjoy doing and taking into account the possibilities of their local context and characteristics [22].…”
Section: Introductionmentioning
confidence: 99%
“…Our research with young people has highlighted the need to provide an age-appropriate self-management solution to help them manage their bladder symptoms [ 8 , 15 ]. This is further supported by the literature on self-management of other health conditions and the growing use of smartphone technology [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 63%